Electromyographic analysis of the surf paddling stroke across multiple intensities - Nessler, J. A.; Ponce-Gonzalez, J. G.; Robles-Rodriguez, C.; Furr, H.; Warner, M.; Newcomer, S. C. (The Journal of Strength and Conditioning Research, 2019)
Surfers spend a majority of their time in the water paddling. The purpose of this study was to examine activity in 5 muscles that contribute to paddling at different velocities and to characterize oxygen use, paddling cadence, and surfboard motion at each velocity. Twelve recreational surfers completed an incremental paddling test on a short surfboard in a swim flume. Surface electromyography was recorded bilaterally from latissimus dorsi, upper and mid trapezius, and posterior and mid deltoid. Electromyographic activity increased as water velocity increased for all muscles, but the change in activation between endurance and sprint paddling was greatest for latissimus dorsi (p < 0.001). At higher water velocities, the middle deltoid was activated earlier in the paddling stroke (p = 0.005). Oxygen use, paddling cadence, and surfboard roll/yaw increased with increasing water velocity. These data may be useful for athletes, trainers, and equipment designers interested in increasing power and efficiency of the paddling stroke.